Measuring Knowledge Management Readiness of Indonesia Ministry of Trade - Dana Indra Sensuse; Jani Richi R. Siregar; Ronny Ansis; Jonathan Sofian Lusa; Pudy Prima (Proceeding of the Electrical Engineering Computer Science and Informatics, 2018)
Knowledge is one of the important assets for organization. Managing knowledge properly will enable the organization to achieve its objectives effectively and efficiently. Since risk of failed implementation of Knowledge Management (KM) might occur, organization needs to measure their KM Readiness beforehand to successfully implement KM. This study is intended to measure KM Readiness in government agency, namely Directorate of Bilateral Negotiations in Ministry of Trade. The research model for measuring KM readiness was developed based on previous relevant studies. KM enablers, individual acceptance, and KM SECI processes were used to develop the model and research instruments. KM Readiness in government agency was measured by accommodating factor analysis in research model. Data were collected from 53 employees as valid samples. The result shows that KM Readiness level of the Directorate of Bilateral Negotiations in Ministry of Trade is "ready but needs a few improvement".